QUR'ANIC RECITATION ART EXTRACURRICULAR ACTIVITY TO IMPROVE STUDENTS' TILAWAH SKILLS AT MTS NEGERI 1 KOTAWARINGIN TIMUR - Miftahul Ilmi; Zainap Hartati; Saiful Lutfi (RADJA PUBLIKA, 2025)
The purpose of this study is to describe the implementation process, impacts, inhibiting and supporting factors of the extracurricular activity of the Art of Reading the Qur'an at MTsN 1 Kotawaringin Timur. The research approach method used in this study is qualitative research. Data collection techniques in this study used observation, interviews, and documentation. The data analysis process obtained in this study began by reviewing all data obtained from interviews, observations and documentation. Furthermore, the data was arranged systematically to make it easier to understand and can provide meaning. The data that has been obtained is then arranged or grouped based on certain categories by going through the stages as stated by Miles and Huberman which include four components, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the extracurricular activity of the Art of Reading the Qur'an at MTsN 1 Kotawaringin Timur is carried out every Thursday afternoon using the classical method. Students are taught the correct tajwid and naghom rhythm to improve tilawah skills. The school supports it with facilities and rewards, although there are obstacles such as inadequate facilities and low student interest. However, this activity remains effective in developing students' recitation skills.